2011
DOI: 10.1108/15982681111140534
|View full text |Cite
|
Sign up to set email alerts
|

The role of Islamic culture in service quality research

Abstract: The purpose: The purpose of this research is to explore Service Quality from the perspective of the Muslim consumer. There is growing evidence that culture influences buying-habits and behaviours' of consumers in services. However, most cross-cultural consumer research in Asia has focused on the dimension of Chinese-Confucian beliefs providing opportunity to investigate other religious-cultural aspects in an Asia and consumption.Design/methodology/approach: This research explores the key attributes/factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 58 publications
(131 reference statements)
3
37
0
Order By: Relevance
“…Yunus et al [36] assurance, tangibles, empathy, responsiveness, reliability, low food prices, short service time and convenient location Based on the previous explanation, it can be concluded that researchers who discussed fast food restaurant service by involving service quality dimensions that represents the performance of service companies in satisfying Muslim customer needs related to Islamic values is very limited. This is quite surprising since Gayatri et al [25]'s research shows the service quality measurement model is influenced by Islamic values of Muslim customers. More specifically, Gayatri and Chew [26] revealed that service quality models of Muslim customers should involve general service quality dimensions and Islamic service quality dimensions.…”
Section: Fast Food Service Quality Modelmentioning
confidence: 79%
See 3 more Smart Citations
“…Yunus et al [36] assurance, tangibles, empathy, responsiveness, reliability, low food prices, short service time and convenient location Based on the previous explanation, it can be concluded that researchers who discussed fast food restaurant service by involving service quality dimensions that represents the performance of service companies in satisfying Muslim customer needs related to Islamic values is very limited. This is quite surprising since Gayatri et al [25]'s research shows the service quality measurement model is influenced by Islamic values of Muslim customers. More specifically, Gayatri and Chew [26] revealed that service quality models of Muslim customers should involve general service quality dimensions and Islamic service quality dimensions.…”
Section: Fast Food Service Quality Modelmentioning
confidence: 79%
“…However, the use of generic service quality model has some problems from both theoretical and practical aspect. Theoretically, researchers have proved that the way of customer on evaluating the quality of service depends on the service contexts, such as service type and customers' culture [24,25,26]. In addition, the proposer of the generic quality models also warned users to consider the specific characteristics of the service industry to be measured when they adopts the generic models [19].…”
Section: Service Quality Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This study will attempt to investigate the variable of service quality with Islamic values, called by Islamic servcice quality. According to Gayatri, Hume, & Mort (2011) reveal that religion is one of the impotant factors in the presence of service quality among Muslims. Thus, this study will propose hypothesis development as a follow:…”
Section: Islamic Service Quality and Zakat Compliance Behaviormentioning
confidence: 99%